KLEDANG FAULT: A STRIKE-SLIP FAULT? - Choong Chee Meng, Askury Abd Kadir, Siti Nur Fathiyah Jamaludin, . (2015)
Kledang Fault is located in the eastern foothill of the Kledang Range in Kinta Valley which has been classified as dip-slip fault by Gobbett (1971). This fault has been clearly observed at regional-scale due to its linear feature and length (> 35km). In our recent outcrop-scale observation, evidences for consistent right-lateral strike-slip fault sets were found along the foothill of southern Kledang Range where they are very close to the location of the Kledang Fault.